2015
DOI: 10.1093/ijnp/pyv065
|View full text |Cite
|
Sign up to set email alerts
|

Salvinorin-A Induces Intense Dissociative Effects, Blocking External Sensory Perception and Modulating Interoception and Sense of Body Ownership in Humans

Abstract: Background:Salvinorin-A is a terpene with agonist properties at the kappa-opioid receptor, the binding site of endogenous dynorphins. Salvinorin-A is found in Salvia divinorum, a psychoactive plant traditionally used by the Mazatec people of Oaxaca, Mexico, for medicinal and spiritual purposes. Previous studies with the plant and salvinorin-A have reported psychedelic-like changes in perception, but also unusual changes in body awareness and detachment from external reality. Here we comprehensively studied the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 42 publications
4
44
0
2
Order By: Relevance
“…Thus, administration of vaporized Sal A to human volunteers leads to intense psychotropic effects including hallucinations, disconnection from external reality, and altered interoceptive abilities (31). To date, it is not known if Collys exhibit hallucinogenic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, administration of vaporized Sal A to human volunteers leads to intense psychotropic effects including hallucinations, disconnection from external reality, and altered interoceptive abilities (31). To date, it is not known if Collys exhibit hallucinogenic effects.…”
Section: Discussionmentioning
confidence: 99%
“…DMN decoupling is also described to occur in psychotic states and after the administration of psychedelic drugs . Most psychedelic drugs (eg, lysergic acid diethylamide, mescaline) are active on a subset of serotonin receptors (5‐HT 2A ), and induce production of complex multimodal hallucinations, delirium, and residual psychosis, whereas the K‐opioid agonist, salvinorin, has been described to induce mind‐body dissociation that breaks the borders of the somatic self and induces a dysperceptive state in which bodily sensations are undifferentiated from external stimuli or autobiographic memories . Drugs acting on these receptors represent potential new targets for SFD‐related research.…”
Section: Anatomical Pathophysiological Overlaps and Mechanismsmentioning
confidence: 99%
“…Several controlled studies have been published recently describing behavioral, subjective, and physiological effects of SA (Addy, 2012; Addy et al, 2015; Johnson et al, 2011; MacLean et al, 2013; Maqueda et al, 2015, 2016; Mendelson et al, 2011; Pichini et al, 2005; Siebert, 1994). None of these studies reported serious adverse events or sustained negative effects.…”
Section: Introductionmentioning
confidence: 99%
“…None of these studies reported serious adverse events or sustained negative effects. Inhaled SA leads to acute psychotomimetic effects (Ranganathan et al, 2012), intense perceptual alterations (Addy, 2012; Addy et al, 2015; MacLean et al, 2013; Ranganathan et al, 2012), dissociative effects (MacLean et al, 2013; Maqueda et al, 2015), elevated cortisol and prolactin, and decreased resting state EEG spectral power (Ranganathan et al, 2012). Peak plasma levels of inhaled SA were found to occur 2 minutes after inhalation, and to directly correspond with participant and observer ratings of subjective effects (Johnson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%